A taxonomic and phylogenetic contribution to Torula: T. phytolaccae sp. nov. on Phytolacca acinosa from China - Li, Yan-Xia; Doilom, Mingkwan; Dong, Wei; Liao, Chun-Fang; Manawasinghe, Ishara Sandeepani; Xu, Biao (Phytotaxa, 2023)
Torula species are commonly reported as saprobes in aquatic and terrestrial habitats worldwide. They have been explored as an interesting source of secondary metabolites. As a result of an investigation of Torula species associated with Phytolacca acinosa in Yunnan, China, T. phytolaccae sp. nov. is described and illustrated. The establishment of a new species is justified based on morphological characteristics and multi-locus phylogenetic analyses. The new species has unique terminal and lateral, monoblastic, doliiform to cupulate conidiogenous cells with phragmosporous, catenate, acrogenous, 2–12-septate, predominantly 3–5-septate, pale brown to dark brown conidia which sometimes consisted of subhyaline to pale brown apex. Phylogenetic analyses of the combined LSU, SSU, ITS, tef1-α and rpb2 sequences generated from maximum likelihood, maximum parsimony and Bayesian inference further showed that T. phytolaccae forms a sister branch with T. herbarum (CBS 246.57), T. hollandica and T. pluriseptata. This study contributes an additional species in Torula with a full description, illustration, and DNA sequences for further contribution toward the circumscription of species in Torula and understanding their phylogenetic relationships.